PERANAN MANAJEMEN SUMBERDAYA MANUSIA DALAM ORGANISASI - Khabib Sharifudin (ADISAM PUBLISHER, 2025)
The purpose of this article is to determine the role of human resource management in an organization. This article uses a literature review method (library research). From the discussion of this article, it can be concluded that human resource management has three functions, namely managerial function, operational function, and function to achieve organizational goals in an integrated manner. While some of the tasks of human resource management are stafl procurement, HR development, managing compensation, managing occupational safety and health, managing work relations and industrial relations. The main purpose of human resource management is to increase the contribution of human resources (employees) to the organization. It can be understood that all organizational activities in achieving their goals depend on the people who manage the organization. Therefore, humans must be managed well so that they can help the organization in achieving the organizational goals that have been determined, in order to achieve the goals of human resource management carried out by HR managers, line managers and outsourcing.